CATALOGUES OF THE FAINT OBJECTS IN THE AREAS WITH GAMMA-RAY BURSTS - Golovnia, V. V.; Protsyuk, Yu. I.; Andruk, V. M.; Vavilova, I. B.; Pakuliak, L. K.; Kulyk, I. V.; Romanyuk, Ya. O.; Baransky, O. R. (Одеські астрономічні публікації, 2016)
The results of GRB observations are being published in the GCN Circulars in real-time. To study all the objects in the sky areas around the GRBs we identified them on the digitized MAO Double Wide angle Astrograph (DWA) plates (D/F=40/200) within a circle with the radius of dozens of arcminutes. We selected only GRBs with the positional accuracy between ±0.3" and ±7.5" and the range of magnitudes between 14m and 20m. We used MIDAS/ROMAFOT package to obtain the catalogues of the faint objects in small areas in the GRBs vicinity. For the plates of DWA telescope the positional rms errors are ± 0.20" for RA and DEC, the photometric errors are ± 0.20m . All positions were obtained in Tycho-2 system.